Project-Based Management Technique for Radiofrequency Spectrum Planning and Allocation: Part One: The Business Case - Kerans, Andrew; Todhunter, Barrie (Journal of Telecommunications and the Digital Economy, 2020)
Spectrum Management is the regulatory action of defining the use of the radiofrequency spectrum. Often this requires the clearance of a large number of incumbent systems to make way for new technologies such as Fourth Generations Mobile Broadband (4G). While great economic benefits may be derived from the new technologies the clearance of any band will come at a cost. It is important both costs and benefits be quantified and compared. In many administrations including Australia these processes are carried out without a defined project management structure. In the first of a series of two papers the Authors combine over 40 years of radio systems and planning experience to suggest a methodology for project-based management of spectrum planning activities.